(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Food adulteration means anything added or subtracted from food, making it injurious tohealth. This adulteration may be done intentionally or unintentionally. Intentional adulteration is acriminal act and a punishable offense. Adulterated food has been linked to various chronic diseaseslike liver disorders, diarrhoea, stomach disorders, lathyrism, cancer, vomiting, dysentery, joint pain,heart diseases, food poisoning, Food products are often a target of adulteration, while supply chainsusually deal with perishable products that could be harmful to consumers if they are not managedproperly. Economic adulteration is a long-term problem affecting the food industry. Adulteration in foodhas been a concern since the beginning of civilization, as it not only decreases the quality of foodproducts but also results in a number of ill effects on health. And the study that discussed thesignificance of food, food adulteration, the nature of adulteration, the impact of adulterants, and so on,The Meaning and Origin of Organic Food The Impact of Food Security in India of Adulterants on Health.